Evaluation of Pansy Varieties as Bedding Plants to Select the Best-of-Class for Florida - Richard O. Kelly; Zhanao Deng; Brent K. Harbaugh (EDIS)
The information in this report is a summary of experimental results and does not provide recommendations for crop production. Where trade names are used, no discrimination is intended or endorsement implied. This document is ENH1031, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date August 2005.